2020
DOI: 10.3389/fpsyg.2020.01757
|View full text |Cite
|
Sign up to set email alerts
|

Tinder Use and Romantic Relationship Formations: A Large-Scale Longitudinal Study

Abstract: The current paper aims to investigate if Tinder use predicts romantic relationship formation 1 year later and to identify demographic, personality, mental health, and substance use covariates in the relationship between Tinder use and romantic relationship formation. Data were collected by online surveys (two waves) among students in Bergen, Norway. The first survey was administered during fall 2015 (T1). The follow-up took place 1 year later (fall 2016, T2). The sample consisted of the 5253 participants who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
4
14
0
Order By: Relevance
“…Dating apps users, although open to short-term relationships, are not reluctant to long-term mating. This converges with previous results as longitudinal higher likelihood of forming romantic the longitudinal by Tinder users [ 34 ] or that previous use is not related to being single [ 10 ]. This pattern of results opens the door to the perception that there may be flexibility in mating orientations and preferences and that they can coexist simultaneously in people seeking both a casual relationship and a romantic relationship [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dating apps users, although open to short-term relationships, are not reluctant to long-term mating. This converges with previous results as longitudinal higher likelihood of forming romantic the longitudinal by Tinder users [ 34 ] or that previous use is not related to being single [ 10 ]. This pattern of results opens the door to the perception that there may be flexibility in mating orientations and preferences and that they can coexist simultaneously in people seeking both a casual relationship and a romantic relationship [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been found that Tinder users have a higher likelihood of forming romantic relationship longitudinally, but that this increased likelihood can be explained by Tinder users’ personality and substance use characteristics [ 34 ]. That previous dating apps use is not related to currently being single [ 10 ] can be interpreted as indicative that users are not relationship-avoidant people.…”
Section: Introductionmentioning
confidence: 99%
“…We discovered that increased use of dating apps was associated with increased risky drinking during the pandemic. Our longitudinal evidence supports previously noted findings that dating app users drink more than nonusers, and this pattern increases during their dates [ 34 - 36 ]. It is likely that alcohol is consumed during the dates, despite bars being closed.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it seems that some social media apps are more popular among risk drinkers. For example, studies on Tinder users have shown that they drink more than nonusers do [ 34 - 36 ]. Dating app users are also more likely to engage in hookups involving alcohol use [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the previous studies have analyzed the role of risky online routines in victimization risk. In this study, we study whether the risky online routines mediate the relationship between ODA use and various sexual and nonsexual victimization experiences while controlling for other relevant risk factors, such as substance abuse (see e.g., Erevik et al, 2020). We will also test the connection between ODA use and online victimization in four national contexts.…”
mentioning
confidence: 99%